CYP2C19 polymorphism and coronary in-stent restenosis: A systematic review and meta-analysis [version 3; peer review: 2 approved, 1 approved with reservations] - Ivana Purnama Dewi; Irawan Yusuf; Agussalim Bukhari; Muzakkir Amir; Vitriyaturrida .; Yusra Pintaningrum; Idar Mappangara; Hendy Bhaskara Perdana Putra (F1000Research)
Background In-stent restenosis (ISR) remains a major drawback in coronary stenting. The association between the CYP2C19 loss of function (LOF) gene and the prevalence of ISR after coronary stenting remains controversial. Previous studies have produced conflicting results and have been limited by their small population sizes. We conducted this systematic review and meta-analysis to determine the association between the presence of the CYP2C19 LOF gene and the prevalence of ISR. Methods A systematic online database search was performed until April 2021. The primary outcome was ISR and assessed using OR with 95% CI. Quality of the study was assessed using the Newcastle Ottawa Scale. I2 was applied to examine heterogeneities among the studies. Results A total of 284 patients (four non-randomized controlled trial studies) were included in this study. Two hundred and six patients had wild-type genotypes, while 78 patients had the LOF genotype. Among the 78 patients with the LOF gene, 38 patients had an ISR. Meanwhile, of the 206 patients with a wild-type gene, 69 patients had an ISR. LOF gene was associated with a higher risk of ISR (OR 95% CI = 2.71 [1.42–5.16], P = 0.003). However, study-specific variability should be considered when applying these findings clinically. Conclusions Patients with LOF genes, regardless of the allele variation, treated with clopidogrel, had a higher likelihood of ISR after coronary stenting.